The Role of Digital Marketing through Social Networks on the Sales of Agricultural Products in "Pajak Horas" - Butar-butar, Diana Florenta; Barus, Ben Setiawan; Nasution, Nurhadida (Journal of Agriculture, 2025)
The agricultural and plantation business sectors face numerous challenges. Intense competition, fluctuating commodity prices, and changing government policies often hinder business actors from increasing their sales and business turnover. Every producer or seller must understand sales improvement strategies and product marketing. Business actors must be able to adapt their sales strategies in response to changing consumer behaviour. In today's digital era, innovative and effective marketing strategies are crucial for success in the agriculture and plantation businesses. With the development of digital technology, these entrepreneurs must keep up with the trend. This study explores whether digital marketing through social media platforms impacts agricultural product sales at the Pematangsiantar Traditional Market. The research method used was quantitative, where data were collected using questionnaires and analysed using SPSS. The data was collected by distributing questionnaires to traditional Pematangsiantar "Pajak Horas" Market traders. A simple linear regression analysis revealed that digital marketing variables, especially those through social media, contributed positively and statistically significantly to sales results. This finding suggests that increasing digital marketing efforts will positively impact agricultural product sales at the Pematangsiantar "Pajak Horas" Market.